Battling COVID-19 and Disasters: Task Force Bureaucracy during Emergencies in the Philippines - S. Perez, Joe-Mar (Policy & Governance Review, 2025)
Coronavirus Disease 2019 (COVID-19) caused significant adjustments in the landscape of public governance in the Philippines. While the world was focused on the pandemic, the Philippines had to simultaneously address the impacts of disasters such as volcanic eruption and strong typhoons. In response, the government resorted to the use of "Task Force", a military concept wherein a unit is designed to work on a single activity. This paper aims to answer the research question: how does the Philippine government operationalize task forces during emergencies such as COVID-19 and other disasters? Using secondary research as methodology, it examines the reconfigurations in the national government in terms of leadership, structure, human capital, policies and practices for disaster management. It analyzes the strengths and challenges of drastic reinventions in public administration and governance while in the middle of a crisis situation wherein all sectors are affected and their implications for the post-pandemic period.